Fixed Point Results for Single and Multivalued Maps on Partial Extended b-Metric Spaces. (23rd May 2022) - Aydi, Hassen; Batul, Samina; Aslam, Muhammad; Sagheer, Dur-e-Shehwar; Ameer, Eskandar
Abstract : This article is based on the concept of partial extended b -metric spaces, which is inspired by the notions of new extended b -metric spaces and partial metric spaces. Fixed point results for single and multivalued mappings on such spaces are also presented. Few examples are also provided to elaborate the concepts.